2022
DOI: 10.1155/2022/3627385
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of Spiral CT and Magnetic Resonance Imaging Scanning in Gastric Cancer and Precancerous Lesions

Abstract: In order to explore the diagnostic value of spiral CT and magnetic resonance imaging scanning in gastric cancer and precancerous lesions, the author selected 56 gastric cancer patients treated in a medical center (group) as the experimental subjects, and all patients underwent MRI, multislice spiral CT scan, and enhanced CT scan two weeks before surgery; at the same time, the gastric cancer staging results of patients were diagnosed according to surgical pathology. All patients were examined under the conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The most popular purpose of using multidimensional spiral computed tomography (MDCT) in gastric cancer is typically to determine the extent of local invasion and the existence or absence of distant metastasis [20]. According to previous research, the T-staging accuracy in spiral CT scanning imaging is 84.5%, with that for the T1 stage even reaching 90.8% [21]. Contrast-enhanced MDCT holds substantial benefits for the diagnosis of gastric cancer (Figure 4C) [22].…”
Section: Multidimensional Spiral Computed Tomographymentioning
confidence: 98%
“…The most popular purpose of using multidimensional spiral computed tomography (MDCT) in gastric cancer is typically to determine the extent of local invasion and the existence or absence of distant metastasis [20]. According to previous research, the T-staging accuracy in spiral CT scanning imaging is 84.5%, with that for the T1 stage even reaching 90.8% [21]. Contrast-enhanced MDCT holds substantial benefits for the diagnosis of gastric cancer (Figure 4C) [22].…”
Section: Multidimensional Spiral Computed Tomographymentioning
confidence: 98%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%